Visual communication in the Indonesian Family Planning Program (1986-2003): a study of a public campaign in Indonesia - Swann, Sandra Tjahjani (Curtin University, 2009)
This thesis is about the visual communication of the national family planning program in Indonesia from 1986 to 2003, which covers three periods: later New Order from 1986 to 1997, Transition in 1998 and early Reformation from 1999 to 2003. This study applies visual social semiotics to the visual images of promotional advertisements from eight campaigns during those 17 years. The study shows that culture is pervasive in these images and that the visual social semiotics framework could only be applied to some extent for reading images of non-Western culture. Visual social semiotics as a methodology provides an accounting framework and is a starting point for interpreting meaning from visual images. From reading the images, there are two themes that play significant roles in understanding the family planning program: nationalism and, family and women. These two themes are deployed in different measure for each period of time to constantly re-define family planning in an engaging and optimal way. However, the technique of visualisation remained the same during the three periods. The practices of looking facilitated by the visual images published for the family planning program positions viewers as Indonesian citizens with a certain morality which generates a general positive attitude about the program. The thesis provides a detailed reading of numerous images from the family planning program; drawing not only on the representation, interaction and composition created by the images but also from analysis of international and state policy on family planning and also the translation of policy into cultural messages.